Da pedra ao pó : granito e megalitismo no Amapá pré-colonial (salpicado de ficção contemporânea das Minas Gerais) - Marina da Silva Costa (2021)
The research deals with the use of granite by indigenous people of the pre-colonial past in Amazonian, near Calçoene town, northern Amapá. It strives for aesthetics through the creative writing seeking greater readers involvement, the research is based on two axes,. the first one presents the use of granite by the indigenous people of the past as antiplastic for making ceramic pots, dug in funerary wells at the Rego Grande I megalithic site (APCA-18, Calçoene / Amapá). This intentional inclusion of the rock was confirmed by petrographic slides made from samples of megalithic ceramics. The second axis of the research seeks to understand a possible symbolic relationship between the granite elements present in the archaeological site and the past of the indigenous peoples who built the megalithic structures, beyond the economist idea of using rock as an simple improvement of pottery. Dialogging archaeological theories and indigenous cosmology through creative writing, it was build a partially fictional narrative, proposing new tools for the archaeological doing.